Safety and efficacy of minimally invasive percutaneous nephrolithotomy for infantile nephrolithiasis. Single centre experience from Pakistan - Ahmad, Tariq; Minallah, Nasrum; Khaliq, Nida; Rashid, Hania; Syed, Misbah; Almuradi, Moath Ahmad Abdullah (Frontiers in Pediatrics, 2023)
Objective: To assess the efficacy and safety of mini-percutaneous nephrolithotomy (PCNL) for small renal stones 1-2 cm in size in infants less than one year. Material and Methods: This descriptive case series was conducted in the department of pediatric urology Institute of Kidney Diseases Peshawar, Pakistan, from March 2019 to March 2022. All the patients underwent mini-PCNL in prone position under GA with 14 Fr access sheath and 10 Fr nephroscope. Stone clearance was assessed by non-contrast CT KUB at 30th postoperative day. Patients with no residual fragments on the non-contrast CT KUB were defined as stone-free. Patients with residual fragments of any size were defined as procedure failure. Safety was determined in terms of intra and postoperative complications. Results: A total of 51 infants were included in the study. The mean age of patients was 9.6+1.8 (5-12 month). The mean stone size was 15.8+2.7 (10-21) mm in length and 12.3+2.2 (8-17) mm in width. PCNL mean operative time was 51.6+/- 7.1 (40-70) minutes. Complete stone clearance at one month was observed in 46 (90.2%) patients. Residual fragments were seen in 5(9.8%) patients with a mean size of 1.6+0.4 (0.9-2.0) mm. None of the patients required any additional procedure for clearance of stones. In 7 (13.7%) patients, some post-operative complications were observe, all were grade I complications, including fever in 5(9.8%) and transient hematuria in 2(3.9%) patients. Conclusion: Mini-PCNL is a safe and effective treatment for renal stones in infants measuring 1-2 cm with high SFR and an acceptable complication rate.